Experimental study on combustion and emission characteristics of LIVC Miller cycle with asynchronous intake valves. (1st December 2022) - Liang, Jichao; Zhang, Quanchang; Chen, Zheng; Qiao, Junhao; Jia, Dongdong; Wang, Rumin; Ma, Qixin; Shen, Dazi
Highlights: Asynchronous LIVC Miller cycle can solve the problem of low combustion efficiency under low loads. Asynchronous LIVC Miller cycle shortened combustion duration and lowered combustion cycle variation. Asynchronous LIVC Miller cycle reduced the BSFC, especially at low and heavy loads. One late intake valve closing can not only improve the knock resistance but also reduce the pump loss effectively. Abstract: An experiment was conducted to explore the performance, combustion, and emission characteristics of the Miller cycle by asynchronous late intake valve closing (LIVC) on a direct-injection turbocharged gasoline engine. Asynchronous LIVC Miller cycle uses geometric compression ratio (GCR) of 12.5:1 (Miller-CR12.5), compared with Otto cycle original engine with GCR of 12.5:1 (Otto-CR12.5) and 10:1 (Otto-CR10). The study indicates that one late intake valve closing can not only realize the Miller cycle but also control the load to effectively reduce the pumping loss. When the brake mean effective pressure (BMEP) is below 4 bar, Miller-CR12.5 shows a very short combustion duration and lower combustion cycle variation compared with the Otto cycle, which solves the problem of low combustion efficiency due to the low actual compression ratio of the Miller cycle. In addition, the Miller cycle of asynchronous LIVC is similar to that of synchronous LIVC, which all can improve knock resistance at medium and high loads. Based on the above factors, Miller-CR12.5 reduces fuel consumption, especially at low and heavy loads. Besides, Miller-CR12.5 shows great fuel-saving potential at high speeds. In terms of emissions, Miller-CR12.5 significantly increases CO and THC emissions within the range of tested loads, but the NOx emissions are reduced under low and high loads.